2018
DOI: 10.31234/osf.io/jxkv3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimentally-Induced Social Threat Increases Paranoid Thinking

Abstract: Fear of others intending harm is central in paranoia but it is unclear to what extent social context alters paranoid attributions, and how this interacts with pre-existing paranoia. We examined social interactions via game theory paradigms across social rank (Experiment 1) and political group affiliation (Experiment 2) as a function of pre-existing paranoia using two pre-registered Dictator Games (N=2,030) for real money. Interacting with someone from a higher social rank or a political out-group led to an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…However, we find this unlikely given that we 547 detected expected relationships between variables, interactions between paranoid 548 ideation and the speed of harmful intent attributions, and found typical population 549 distributions of anxiety, worry and paranoia. Similarly, 'screen-based' studies have 550 previously reported reliable effects when testing paranoid ideation (29)(30)(31)(32)(33)(50)(51)(52). 551…”
Section: Discussion 492mentioning
confidence: 97%
See 2 more Smart Citations
“…However, we find this unlikely given that we 547 detected expected relationships between variables, interactions between paranoid 548 ideation and the speed of harmful intent attributions, and found typical population 549 distributions of anxiety, worry and paranoia. Similarly, 'screen-based' studies have 550 previously reported reliable effects when testing paranoid ideation (29)(30)(31)(32)(33)(50)(51)(52). 551…”
Section: Discussion 492mentioning
confidence: 97%
“…Participants make decisions that 56 have outcomes with genuine gains and losses and therefore real, albeit small, harms 57 and benefits (29,25). Existing research has shown that increases in harmful intent 58 attributions are associated with trait paranoia, social threat (29,30), social cohesion 59 of task partners (31), and increased relative social rank, and outgroup status, of the 60 interaction partner (32). However, current game theory paradigms in paranoia 61 research that have allowed for participant-to-participant (rather than simulated; 16, 62 17) interactions have tended to use single round games or brief interactions that are 63 not able to test the effect of paranoia and additional psychological variables on 64 attributions over evolving interactions .…”
Section: Background 22mentioning
confidence: 99%
See 1 more Smart Citation
“…These results also imply that the relationship between competitive status and aggression is not limited to 193 situations involving face-to-face competition, but also applies to virtual, indirect contests. In line with this 194 assumption, an online bargaining study showed that individuals attribute more hostile intentions to higher-195 status opponents [36]. Competitive status thus appears to be a relevant trigger for aggressive behavior in 196 both direct and virtual interactions.…”
Section: Discussion 176mentioning
confidence: 88%
“…Concerning hormonal concentrations, testosterone increased after scanning (t=2.10, d=. 36,122 p=.040; Fig. 2d) whereas cortisol decreased (t=4.96, d=.92, p<.001; Fig.…”
mentioning
confidence: 95%